2015
DOI: 10.1007/s00535-015-1050-7
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based clinical practice guidelines for nonalcoholic fatty liver disease/nonalcoholic steatohepatitis

Abstract: Nonalcoholic fatty liver disease (NAFLD) is currently the most common cause of chronic liver disease in industrialized countries worldwide, and has become a serious public health issue not only in Western countries but also in many Asian countries including Japan. Within the wide spectrum of NAFLD, nonalcoholic steatohepatitis (NASH) is a progressive form of disease, which often develops into liver cirrhosis and increases the risk of hepatocellular carcinoma. In turn, a large proportion of NAFLD/NASH is the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
133
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 226 publications
(141 citation statements)
references
References 137 publications
1
133
0
2
Order By: Relevance
“…1,[5][6][7] Therefore, epigenetic modifications, either inherited or induced by lifestyles, 8,9 may play a key role in the pathogenesis of the disease. To some extent, the epigenetic mechanisms resulting in aberrant histone modifications, differences in DNA methylation, and dysregulation of microRNAs are the ones that have been related to NAFLD and its transition to more advanced stages.…”
Section: Introductionmentioning
confidence: 99%
“…1,[5][6][7] Therefore, epigenetic modifications, either inherited or induced by lifestyles, 8,9 may play a key role in the pathogenesis of the disease. To some extent, the epigenetic mechanisms resulting in aberrant histone modifications, differences in DNA methylation, and dysregulation of microRNAs are the ones that have been related to NAFLD and its transition to more advanced stages.…”
Section: Introductionmentioning
confidence: 99%
“…Cusi et al recently reported on the beneficial effects of pioglitazone on NASH in patients with prediabetes or type 2 diabetes mellitus [15]. However, the only established therapies for NAFLD are dietary and exercise therapies [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Nonalcoholic fatty liver disease (NAFLD), which is the most common chronic liver disease worldwide, is classified into nonalcoholic fatty liver (NAFL) and nonalcoholic steatohepatitis (NASH) [1,2]. The prevalence of NAFLD has increased with the rise in obesity and metabolic syndrome and is associated with lifestyle changes.…”
Section: Introductionmentioning
confidence: 99%
“…NAFLD includes non-alcoholic fatty liver (NAFL) and non-alcoholic steatohepatitis (NASH), with NAFL representing the first phase of NASH. NASH, which is characterized by steatosis, can subsequently develop into fatty liver disease with associated inflammation, with the potential to result in cirrhosis and/or hepatocellular carcinoma (3). The increased number of young patients with NAFLD/NASH associated with metabolic syndrome has therefore become an important epidemiologic problem (1).…”
Section: Introductionmentioning
confidence: 99%